1997
DOI: 10.1017/s0021859696003759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant density on intercropped wheat and field beans in an organic farming system

Abstract: In field trials in 1987\88 near Pangbourne, England, wheat (Triticum aestivum) and field beans (Vicia faba) were grown in an organic farming system as sole crops and additive intercrops. The sole crops were grown at 25, 50, 75, 100 and 150 % of the recommended density (RD) for conventionally grown crops. The intercrops consisted of all density combinations of wheat and beans from 25 to 100 % RD in a factorial experiment. The grain yield of sole cropped wheat and beans increased significantly as their density w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
117
1
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 35 publications
16
117
1
7
Order By: Relevance
“…Different findings have been reported by Haymes and Lee (1999) who observed yield benefit when field beans was sown in the intercrop at 100% and wheat at 50% of recommended pure stand density or the species were sown in the intercrop at 100% of their recommended pure stand densities. Bulson et al (1997) noted the highest yield advantage of wheat-field beans intercrop when both components were sown at 75% of recommended pure stand density. Unlike the experiment reported here both studies were conducted in more productive soil conditions that were suitable for both crops.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Different findings have been reported by Haymes and Lee (1999) who observed yield benefit when field beans was sown in the intercrop at 100% and wheat at 50% of recommended pure stand density or the species were sown in the intercrop at 100% of their recommended pure stand densities. Bulson et al (1997) noted the highest yield advantage of wheat-field beans intercrop when both components were sown at 75% of recommended pure stand density. Unlike the experiment reported here both studies were conducted in more productive soil conditions that were suitable for both crops.…”
Section: Discussionmentioning
confidence: 92%
“…According to Austin et al (1988) It means the competing species use partially different growing resources or utilize the same resources but more efficiently due to differences in plant architecture, physiology or growing cycle (Bulson et al 1997). If there is no competition between species RYT = 2.0.…”
Section: Methodsmentioning
confidence: 99%
“…Intercrops can potentially reduce weeds, diseases and pests (Trenbath 1993;Altieri 1999) often regarded as determinant factors influencing crop production (Liebman 1988;White and Scott 1991;Liebman and Dyck 1993;Midmore 1993;Bulson et al 1997;Liebman and Davis 2000;HauggaardNielsen et al 2001b). In particular, grain legumes, such as peas (P. sativum L.), are known to be weak competitors against weeds when grown as the sole crop (Wall et al 1991;Townley-Smith and Wright 1994;Mcdonald 2003), and weed infestations have been shown to severely limit the N nutrition and grain yield of organically grown grain legumes (Corre-Hellou and Crozat 2005).…”
Section: Intercropping Reduce Weeds Compared To the Sole Cropped Legumesmentioning
confidence: 99%
“…For instance, Bulson et al (1997) found that weed biomass was significantly reduced when the densities of wheat (Triticum aestivum L.) and field bean (Vicia faba L.) intercrops were increased; and Arce et al (2009) showed that soybean seeding rates (24Á42 seeds/m 2 ) were inversely related to weed biomass. Increased seeding rates lead to quicker canopy closure, increased crop interference and greater weed suppression, resulting in increased yields (Olsen et al 2006;Kolb et al 2012).…”
Section: Research Articlementioning
confidence: 99%